Damage assessment using advanced non-intrusive inspection methods: integration of space, UAV, GPR, and field spectroscopy - Themistocleous, Kyriacos; Neocleous, Kyriacos; Pilakoutas, Kipros; Hadjimitsis, Diofantos G. (My University, 2014)
The predominant approach for conducting road condition surveys and analyses is still largely based on extensive field observations. However, visual assessment alone cannot identify the actual extent and severity of damage. New non-invasive and cost-effective non-destructive (NDT) remote sensing technologies can be used to monitor road pavements across their life cycle, including remotely sensed aerial and satellite visual and thermal image (AI) data, Unmanned Aerial Vehicles (UAVs), Spectroscopy and Ground Penetrating Radar (GRP). These non-contact techniques can be used to obtain surface and sub-surface information about damage in road pavements, including the crack depth, and in-depth structural failure. Thus, a smart and cost-effective methodology is required that integrates several of these non-destructive/ no-contact techniques for the damage assessment and monitoring at different levels. This paper presents an overview of how an integration of the above technologies can be used to conduct detailed road condition surveys. The proposed approach can also be used to predict the future needs for road maintenance; this information is proven to be valuable to a strategic decision making tools that optimizes maintenance based on resources and environmental issues. © (2014) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.
Keywords: Field spectroscopy; Ground penetrating radar; Inspection; Unmanned aerial vehicles; Roads; Satellites; Spectroscopy; Remote sensing